2016
DOI: 10.3989/gya.0337161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <em>Thymus vulgaris</em> and <em>Bunium persicum</em> essential oils on the oxidative stability of virgin olive oil

Abstract: SUMMARY:Natural antioxidants are becoming a major focus because natural food ingredients are safer than synthetic types. The aim of this study was to investigate the protective effects of Thymus vulgaris and Bunium persicum essential oils (EO) on the oxidation of virgin olive oil (VOO) during accelerated storage. The antioxidant activities of EOs were compared with those of α-tocopherol and BHT. GC/MS analyses revealed that thymol (28.50%), p-cymene (27.14%), carvacrol (18.36%), and γ-terpinene (4.97%) are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Oil samples stored in amber bottles with no added antioxidant showed an increment in the oxidation parameters (peroxide, p-anisidine, and total oxidation values) after the 35th day while aromatized oil slowed down this increment. Similarly, the presence of the T. vulgaris essential oil also delayed the formation of conjugated dienes and trienes and protected the chlorophyll and carotenoid contents providing similar results to with BHT [86]. The addition of 0.05% of O. vulgare essential oil to EVOO was demonstrated to improve the preservation of the chlorophyll content, with a final concentration of 3.87 mg/kg after 28 days of storage in darkness but also under the temperature treatment.…”
Section: Potential Strategies To Preserve Evoossupporting
confidence: 52%
“…Oil samples stored in amber bottles with no added antioxidant showed an increment in the oxidation parameters (peroxide, p-anisidine, and total oxidation values) after the 35th day while aromatized oil slowed down this increment. Similarly, the presence of the T. vulgaris essential oil also delayed the formation of conjugated dienes and trienes and protected the chlorophyll and carotenoid contents providing similar results to with BHT [86]. The addition of 0.05% of O. vulgare essential oil to EVOO was demonstrated to improve the preservation of the chlorophyll content, with a final concentration of 3.87 mg/kg after 28 days of storage in darkness but also under the temperature treatment.…”
Section: Potential Strategies To Preserve Evoossupporting
confidence: 52%
“…Talebi et al (2017) indicated that polylactic acid films containing BPEO may be useful for packaging of foods in order to increase their shelf life and safety. Studies in the field of maintenance and oxidative stability of various types of edible oils such as olive, Linseed and soybean oil have confirmed that BP essential oil can be used as food additive and a natural antioxidant compound to increase the shelf life and oxidative stability of oils (Keramat and Golmakani, 2016;Shahsavari et al, 2008;Zangiabadi et al, 2013).…”
Section: Application In Food Systemsmentioning
confidence: 99%
“…Also, antioxidant indices of the samples were estimated and were reported as the induction period (IP), protection factor (PF), antioxidant activity (AA), improved oxidative stability (IOS), and synergism degree resulting from the combination of antioxidants. The IP is defined as the number of days necessary to reach the PV of 20 meq O 2 /kg (Keramat and Golmakani, 2016). The IP was calculated by the extrapolation of PV curve.…”
Section: Oxidative Stability Of Olive Oil Incorporated With Spirulinamentioning
confidence: 99%